Disinhibition of olfactory bulb granule cells accelerates odour discrimination in mice - Nunes, Daniel; Kuner, Thomas (Nature Communications, 2015)
Granule cells are the dominant cell type of the olfactory bulb inhibiting mitral and tufted cells via dendrodendritic synapses; yet the factors regulating the strength of their inhibitory output, and, therefore, their impact on odour discrimination, remain unknown. Here we show that GABAAR β3-subunits are distributed in a somatodendritic pattern, mostly sparing the large granule cell spines also known as gemmules. Granule cell-selective deletion of β3-subunits nearly abolishes spontaneous and muscimol-induced currents mediated by GABAA receptors in granule cells, yet recurrent inhibition of mitral cells is strongly enhanced. Mice with disinhibited granule cells require less time to discriminate both dissimilar as well as highly similar odourants, while discrimination learning remains unaffected. Hence, granule cells are controlled by an inhibitory drive that in turn tunes mitral cell inhibition. As a consequence, the olfactory bulb inhibitory network adjusts the speed of early sensory processing.